Development in fish vaccinology with focus on delivery methodologies, adjuvants and formulations - Evensen O. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
Sustainable development in aquaculture is equivalent to disease prevention, and vaccination has become the single most important tool. There has been a dramatic reduction in use of antibiotics in Norwegian salmon farming since the introduction of oil-based vaccines. Today, it is an industry standard in all salmon-producing countries, and we are seeing a similar approach being adopted in Japan for farming high value species. Fish can be vaccinated by immersion and the oral route, however, the protection falls short compared to injection vaccination. Interesting new technologies have emerged over the last 5 years, particularly injection of a single dose of naked DNA into the fish muscle. Nevertheless, the prospect of having a commercial product on the market within 5 years is meagre. New technologies are promising but it is more likely there will be improvements of existing vaccines than completely new technologies taking over the fish vaccination scene in the next 5-10 years.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)